2022
DOI: 10.1051/0004-6361/202142723
|View full text |Cite
|
Sign up to set email alerts
|

The merging process of chromospheric fibrils into a filament

Abstract: Context. Although solar filaments have been intensively studied, detailed observations that show an entire process of filament maintenance are rare. Aims. The aim of this paper is to study the whole process of the material supply and the magnetic flux injection from chromospheric fibrils to a nearby filament. Methods. Based on multiwavelength observations from the New Vacuum Solar Telescope and the Solar Dynamics Observatory (SDO), we tracked the evolution of the chromospheric fibrils involved in the process o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…However, numerical simulations and high-resolution observations have found that filament materials are usually in a cyclic state, which is characterized by the dynamic balance between the drainage of filament materials back to the chromosphere and the formation of filament materials transferred from the low atmosphere to the corona (Engvold 1976;Berger et al 2008;Chae et al 2008;Xia et al 2016). Three models have been proposed to explain the formation of filament materials: injection model (Chae et al 2001), levitation model (Poland & Mariska 1986;Lites 2005;Fang et al 2022), and evaporation-condensation model (Antiochos et al 2000;Kaneko & Yokoyama 2017). About the drainage of filament materials, observational results have displayed that filament materials fall back to the lower chromosphere either along the barbs (Dai et al 2021) or the footpoints (Seaton et al 2011;Bi et al 2014).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…However, numerical simulations and high-resolution observations have found that filament materials are usually in a cyclic state, which is characterized by the dynamic balance between the drainage of filament materials back to the chromosphere and the formation of filament materials transferred from the low atmosphere to the corona (Engvold 1976;Berger et al 2008;Chae et al 2008;Xia et al 2016). Three models have been proposed to explain the formation of filament materials: injection model (Chae et al 2001), levitation model (Poland & Mariska 1986;Lites 2005;Fang et al 2022), and evaporation-condensation model (Antiochos et al 2000;Kaneko & Yokoyama 2017). About the drainage of filament materials, observational results have displayed that filament materials fall back to the lower chromosphere either along the barbs (Dai et al 2021) or the footpoints (Seaton et al 2011;Bi et al 2014).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…To determine which physical mechanism triggering these propagating knots, we examine all the NVST Hα observations over the past decade. The examples (Yang et al 2015;Fang et al 2022) of unambiguous magnetic reconnection between chromospheric fibrils are no more than 15, implying that magnetic reconnection between fibrils is difficult to occur (or at least difficult to be detected). Besides, all the examples show that magnetic reconnection occurs between fibrils with oppositepolarity fields.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…For explaining the source of filament material, three types of models are proposed. They are the levitation model (Poland et al 1986;Zhao et al 2017;Fang et al 2022), injection model (An et al 1988;Chae 2003;Liu et al 2005;Wang et al 2019), and evaporation-condensation model (Antiochos et al 2000;Li et al 2019;Yang et al 2021;Zhao & Keppens 2022). In the levitation model, cool chromospheric plasma can be carried by the rising magnetic field and lifted to the corona to form filament (Fang et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…They are the levitation model (Poland et al 1986;Zhao et al 2017;Fang et al 2022), injection model (An et al 1988;Chae 2003;Liu et al 2005;Wang et al 2019), and evaporation-condensation model (Antiochos et al 2000;Li et al 2019;Yang et al 2021;Zhao & Keppens 2022). In the levitation model, cool chromospheric plasma can be carried by the rising magnetic field and lifted to the corona to form filament (Fang et al 2022). As for the injection model, filament material can be fed by magnetic reconnection in the form of jets or surge (Liu et al 2005;Wang et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation